(untitled) (Update Dental College Journal, 2015)
Class II malocclusion is the condition in which the mandibular first molars occlude distal to the normal relationship with the maxillary first molar. The etiology of class II malocclusion varied between skeletal, soft tissues, dental factors and habits. Skeletal class II could be because of protrusion of maxilla, retrusion of mandible and combination of both. The treatment modalities of any skeletal problem include Growth modification, Dental camouflage and Orthognathic surgery. The optimal time for treatment of patients with Class II malocclusions therapy should be initiated at the beginning of cervical vertebrae maturation stage CS3 to maximize the treatment effects. Age of treatment is approximately 8-14 years. The growth modification of moderate to severe skeletal class II malocclusion can be done by head gear, bionator, activator, twin block, herbest appliance, Frankel II regulator. The ultimate goal of growth modification depends on treatment timing, length of treatment, working mechanism of appliance, patients skeletal and dental condition we want to treat and the compliance of the patient. Update Dent. Coll. j: 2014; 4 (2): 23-26